Ground self-leveling mortar based on copper tailing waste residues and preparation method of ground self-leveling mortar
By preparing ground self-leveling mortar based on copper tailings waste slag, the problem of low resource utilization rate of copper tailings waste slag is solved, efficient and low-cost resource utilization and excellent mortar production are achieved, and market demand is met.
Patent Information
- Application Number
- CN202411461556.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-01-07
AI Technical Summary
The resource utilization rate of copper tailings waste slag is low, resulting in secondary pollution, complex production processes and high costs, making it difficult to meet the needs of the special mortar market.
The ground self-leveling mortar based on copper tailings waste slag and its preparation method are used to prepare high-performance mortar that meets national standards through drying and particle grading, combined with quartz powder, silicate cement and other materials to realize copper tailings waste slag full component replacement and efficient utilization.
The resource utilization of copper tailings waste slag has been achieved, which significantly reduces production costs, increases the added value of mortar, meets the performance requirements of ground self-leveling mortar, and simplifies the production process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of industrial solid waste resource application, and in particular to a ground self-leveling mortar based on copper tailings waste and a preparation method thereof. Background Art
[0002] Since the metal grade of the original ore of non-ferrous mines is low, the tailings yield is high, and the amount of tailings accumulation is increasing. The storage of tailings will occupy a large amount of land resources and cause serious pollution to the surrounding environment. The harm of tailings is serious, so it is necessary to strengthen the management and comprehensive utilization of tailings.
[0003] At present, there are many directions for the resource utilization of copper tailings, but its comprehensive utilization rate is only about 30%. The main reasons why related results are difficult to industrialize are: copper tailings from different origins have large differences in chemical composition, mineral composition and other aspects, and it is difficult to directly copy the resource utilization plan and process in the process of promotion and application; the proportion of useful components that can be resourced is low. For each resource utilization direction, the proportion of resource-usable components in copper tailings is low, and a large amount of residual copper tailings waste needs to be secondary processed, stored or landfilled; the harmful components in copper tailings are limited in the proportion of copper tailings that can be resource-utilized in order to ensure that the sand used meets relevant standards and does not affect the quality of downstream products; the added value of resource-utilized products developed for building materials products is not high, resulting in the limited radiation range of downstream products under the premise of market price competitiveness. On the other hand, with the improvement of people's requirements for the quality of home life and the accelerated advancement of old-town renovation, the market demand for special mortars including self-leveling mortars is growing rapidly. The special sand used in the production of special mortars is ultra-fine sand, which has high requirements on the quality of sand and gravel resources and high energy consumption in production. The remaining tailings waste (fineness modulus is only about 0.3, and powder content exceeds 25%) after recovering valuable minerals from copper tailings is used to prepare special mortars, which can consume large quantities of copper tailings waste and give full play to the relevant characteristics of copper tailings waste.
[0004] At present, there are a few technical developments on the application of copper tailings to special mortars, such as: CN 106892581 B discloses a plaster mortar for external wall insulation prepared by using fine sand from mine tailings and a preparation method thereof, in which the fine sand from mine tailings is graded into three gradation areas of 0.10≤particle size<0.15mm, 0.15mm≤particle size<0.20mm, and 0.20mm≤particle size<0.40mm, and is combined in a certain proportion. The invention divides the fine sand from mine tailings into three gradations, and the mine tailings after combined grading can completely replace river sand. The prepared plaster mortar for external wall insulation has excellent performance and fully meets the various performance index requirements of GB / T25181-2010 for plaster mortar. In addition, the cost of the plaster mortar for external wall insulation prepared by fine sand from mine tailings is significantly reduced, and the cost of each ton of plaster mortar for external wall insulation is reduced by more than 45 yuan.
[0005] CN 101880142 B discloses a method for preparing wall and floor tile bonding mortar by using mine tailings. The method adopts the following components in weight ratio: 50-250 parts of silicate cement, 20-150 parts of fly ash, 100-650 parts of iron tailings sand or copper tailings sand, 1-18 parts of redispersible latex powder, and 0.2-0.6 parts of water reducing agent. The preparation method is: drying the iron tailings sand or copper tailings sand to make the moisture content of 1%-6%, and then mixing with silicate cement, fly ash, water reducing agent, and redispersible polymer latex powder in a zero-gravity mixer to form a dry powder mortar product. The invention utilizes a large amount of industrial and mining solid waste iron tailings sand or copper tailings sand, fly ash, etc., and improves the mortar performance, especially the bonding performance, by compounding the redispersible polymer latex powder to prepare high-performance environmentally friendly wall and floor tile bonding mortar.
[0006] At present, there are few studies on the resource utilization and production process of copper tailings waste after the recovery of valuable components. With the core goals of solving the secondary pollution of copper tailings waste, improving resource utilization rate and added value, simplifying production process and reducing production costs, the development of special mortars such as self-leveling mortar for the ground that can absorb copper tailings waste on a large scale is of great significance. Summary of the invention
[0007] In view of the problems of low resource utilization rate of existing copper tailings waste, the present invention provides a ground self-leveling mortar based on copper tailings waste and a preparation method thereof.
[0008] Implementation method of the present invention: A ground self-leveling mortar based on copper tailings waste, calculated by weight: 50-150 parts of 0-0.045mm quartz stone powder, 50-150 parts of 0-0.075mm copper tailings waste powder, 40-60 parts of 0.075-0.15mm copper tailings waste, 150-200 parts of 0.15-0.3mm copper tailings waste, 30-60 parts of 0.3-0.6mm copper tailings waste , 180-220 parts of 0.3-0.6mm quartz sand, 230-270 parts of P·O42.5 cement, 80-120 parts of sulphoaluminate cement, 20-40 parts of anhydrite, 0.8-0.9 parts of tartaric acid, 6-8 parts of redispersible latex powder, 0.6-0.8 parts of cellulose ether, 0.8-1.0 parts of water reducer, 200-240 parts of water; the copper tailings waste residue is the waste residue after the valuable components of the copper tailings are recovered. In the present invention, the copper tailings waste residue meets the relevant index requirements of Class A decoration materials in "Limits of Radioactive Nuclides in Building Materials" GB6566; the cellulose ether meets the relevant index requirements of "Cellulose Ether for Building Dry Mix Mortar" JC / T 2190, and the viscosity is not less than 400mPa·s; the redispersible latex powder meets the relevant index requirements of "Redispersible Latex Powder for Building Dry Mix Mortar" JC / T 2189.
[0009] Preferably, the cellulose ether is hydroxypropyl methylcellulose with a viscosity of 400 mPa·s.
[0010] Preferably, the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer.
[0011] Preferably, the water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate of 25-30%.
[0012] Preferably, the copper tailings waste has a moisture content of less than 0.5%.
[0013] The preparation method of the above-mentioned copper tailings waste slag-based floor self-leveling mortar comprises the following steps: step 1, drying: using a drying equipment to dry the copper tailings waste slag after valuable components are recovered, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle grading of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag of 0.075-0.6 mm to ensure that the copper tailings waste slag with suitable grading components is obtained after screening and adjustment; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradings, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 2-5 minutes, and then water is added and stirred for 4-8 minutes to obtain a floor self-leveling mortar based on copper tailings waste slag.
[0014] Beneficial effects of the present invention:
[0015] (1) Based on the particle size distribution and particle morphology characteristics of copper tailings waste particles, combined with its low water demand and other characteristics, the present invention proposes a ground self-leveling mortar based on copper tailings waste and a preparation method thereof, which not only embodies the "full use and full use of solid waste", but also realizes the "high quality and best use" based on the characteristics of the solid waste itself.
[0016] (2) The 0-0.075 mm copper tailings waste powder replaces the traditional quartz powder and heavy calcium powder, and the 0.075-0.6 mm graded copper tailings waste replaces the natural ultra-fine sand, thus achieving full component replacement from powder to fine aggregate. Combined with the particle size distribution characteristics of copper tailings waste and process adjustment, the resource utilization of copper tailings waste can be nearly 100%.
[0017] (3) The self-leveling mortar prepared from copper tailings waste has excellent performance, and its performance indicators meet the requirements of national and industry standards such as "Premixed Mortar" GB / T25181 and "Self-leveling Mortar" JC / T 985.
[0018] (4) The method for preparing the ground self-leveling mortar based on copper tailings waste slag proposed in the present invention has a simple and feasible process, saves energy and reduces consumption, and can significantly improve the scope of application and resource utilization rate of preparing the ground self-leveling mortar based on copper tailings waste slag.
[0019] (5) The amount of copper tailings waste slag added to the self-leveling mortar of the present invention can reach about 50% by mass ratio. The cost of copper tailings waste slag is low. Compared with the use of specially prepared natural extra-fine sand, quartz powder / heavy calcium powder, etc., the production cost of the self-leveling mortar is significantly reduced (calculated based on the current price of Guangxi sand and gravel resources, quartz powder, and heavy calcium powder in 2023, the production cost of each ton of self-leveling mortar using copper tailings waste slag can be reduced by nearly RMB 50 or more), and the self-leveling mortar product has high added value. The invention effectively solves the problem of copper tailings waste slag treatment, and has significant environmental and economic benefits. DETAILED DESCRIPTION
[0020] The specific embodiments of the present invention are described in detail below, but it should be understood that the protection scope of the present invention is not limited by the specific embodiments.
[0021] Embodiment 1:
[0022] A self-leveling mortar based on copper tailings waste, calculated by weight: 50 parts of 0-0.045mm quartz powder, 150 parts of 0-0.075mm copper tailings waste powder, 40 parts of 0.075-0.15mm copper tailings waste, 200 parts of 0.15-0.3mm copper tailings waste, 60 parts of 0.3-0.6mm copper tailings waste, 180 parts of 0.3-0.6mm quartz sand, P·O42.5 270 parts of cement, 80 parts of sulphoaluminate cement, 20 parts of anhydrite, 0.8 parts of tartaric acid, 6 parts of redispersible latex powder, 0.8 parts of cellulose ether, 0.8 parts of water reducing agent, and 240 parts of water; wherein the moisture content of copper tailings waste slag of various particle sizes is less than 0.5%, the cellulose ether is hydroxypropyl methylcellulose (viscosity 400mPa·s), the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0023] The method for preparing the above-mentioned copper tailings waste slag-based self-leveling mortar for the ground comprises the following steps: step 1, drying: drying the copper tailings waste slag after valuable components are recovered by using drying equipment, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag with a size of 0.075-0.6 mm, to ensure that the copper tailings waste slag with a suitable graded composition is obtained after screening and adjustment; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 2 minutes, and then water is added and stirred for 4 minutes to obtain the copper tailings waste slag-based self-leveling mortar for the ground.
[0024] Embodiment 2:
[0025] A self-leveling mortar based on copper tailings waste, calculated by weight: 75 parts of 0-0.045mm quartz powder, 125 parts of 0-0.075mm copper tailings waste powder, 45 parts of 0.075-0.15mm copper tailings waste, 180 parts of 0.15-0.3mm copper tailings waste, 55 parts of 0.3-0.6mm copper tailings waste, 190 parts of 0.3-0.6mm quartz sand, P·O42.5 cement 260 parts, 90 parts of sulphoaluminate cement, 25 parts of anhydrite, 0.85 parts of tartaric acid, 6.5 parts of redispersible latex powder, 0.75 parts of cellulose ether, 0.85 parts of water reducing agent, and 230 parts of water; wherein the moisture content of copper tailings waste slag of each particle size is less than 0.5%, the cellulose ether is hydroxypropyl methylcellulose (viscosity 400mPa·s), the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0026] The method for preparing the above-mentioned copper tailings waste slag-based self-leveling mortar for the ground comprises the following steps: step 1, drying: using a drying device to dry the copper tailings waste slag after valuable components are recovered, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag with a size of 0.075-0.6 mm, to ensure that the copper tailings waste slag with a suitable graded composition is obtained after screening and adjustment; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 3 minutes, and then water is added and stirred for 5 minutes to obtain the copper tailings waste slag-based self-leveling mortar for the ground.
[0027] Embodiment 3:
[0028] A self-leveling mortar based on copper tailings waste, calculated by weight: 100 parts of 0-0.045mm quartz stone powder, 100 parts of 0-0.075mm copper tailings waste powder, 50 parts of 0.075-0.15mm copper tailings waste, 170 parts of 0.15-0.3mm copper tailings waste, 50 parts of 0.3-0.6mm copper tailings waste, 200 parts of 0.3-0.6mm quartz sand, P·O42.5 250 parts of cement, 100 parts of sulphoaluminate cement, 30 parts of anhydrite, 0.9 parts of tartaric acid, 7 parts of redispersible latex powder, 0.7 parts of cellulose ether, 0.9 parts of water reducing agent, and 220 parts of water; wherein the moisture content of copper tailings waste slag of various particle sizes is less than 0.5%, the cellulose ether is hydroxypropyl methylcellulose (viscosity 400mPa·s), the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0029] The method for preparing the above-mentioned copper tailings waste slag-based self-leveling mortar for the ground comprises the following steps: step 1, drying: using a drying device to dry the copper tailings waste slag after valuable components are recovered, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag with a size of 0.075-0.6 mm, to ensure that the copper tailings waste slag with a suitable graded composition is obtained after screening and mixing; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 4 minutes, and then water is added and stirred for 6 minutes to obtain the copper tailings waste slag-based self-leveling mortar for the ground.
[0030] Embodiment 4:
[0031] A self-leveling mortar based on copper tailings waste, calculated by weight: 125 parts of 0-0.045mm quartz powder, 75 parts of 0-0.075mm copper tailings waste powder, 55 parts of 0.075-0.15mm copper tailings waste, 160 parts of 0.15-0.3mm copper tailings waste, 45 parts of 0.3-0.6mm copper tailings waste, 210 parts of 0.3-0.6mm quartz sand, 200 parts of P·O42.5 cement 40 parts, sulphoaluminate cement 110 parts, anhydrite 35 parts, tartaric acid 0.85 parts, redispersible latex powder 7.5 parts, cellulose ether 0.65 parts, water reducer 0.95 parts, water 210 parts; wherein the moisture content of copper tailings waste slag of each particle size is less than 0.5%, the cellulose ether is hydroxypropyl methylcellulose (viscosity 400mPa·s), the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer, and the water reducer is a polycarboxylic acid water reducer.
[0032] The preparation method of the above-mentioned copper tailings waste slag-based ground self-leveling mortar comprises the following steps: step 1, drying: using a drying device to dry the copper tailings waste slag after valuable components are recovered, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag with a size of 0.075-0.6 mm, to ensure that the copper tailings waste slag with a suitable graded composition is obtained after screening and mixing; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 5 minutes, and then water is added and stirred for 7 minutes to obtain the ground self-leveling mortar based on the copper tailings waste slag.
[0033] Embodiment 5:
[0034] A self-leveling mortar based on copper tailings waste, calculated by weight: 150 parts of 0-0.045mm quartz powder, 50 parts of 0-0.075mm copper tailings waste powder, 60 parts of 0.075-0.15mm copper tailings waste, 150 parts of 0.15-0.3mm copper tailings waste, 40 parts of 0.3-0.6mm copper tailings waste, 220 parts of 0.3-0.6mm quartz sand, P·O42.5 230 parts of cement, 120 parts of sulphoaluminate cement, 40 parts of anhydrite, 0.8 parts of tartaric acid, 8 parts of redispersible latex powder, 0.6 parts of cellulose ether, 1.0 parts of water reducing agent, and 200 parts of water; wherein the moisture content of copper tailings waste slag of various particle sizes is less than 0.5%, the cellulose ether is hydroxypropyl methylcellulose (viscosity 400mPa·s), the main component of the redispersible latex powder is ethylene-vinyl acetate copolymer, and the water reducing agent is a polycarboxylic acid water reducing agent.
[0035] The method for preparing the above-mentioned copper tailings waste slag-based self-leveling mortar for the ground comprises the following steps: step 1, drying: using a drying device to dry the copper tailings waste slag after valuable components are recovered, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: using a vibration screening process to screen the copper tailings waste slag with a size of 0.075-0.6 mm, to ensure that the copper tailings waste slag with a suitable graded composition is obtained after screening and adjustment; step 3, mixing and stirring: first, quartz powder, copper tailings waste slag powder, copper tailings waste slag of different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducer are added to a mixer after metering and mixed for 4 minutes, and then water is added and stirred for 8 minutes to obtain the copper tailings waste slag-based self-leveling mortar for the ground.
[0036] The application performance of a self-leveling mortar based on copper tailings waste prepared in Example 1 to Example 5 was tested. The performance test was based on the technical index requirements and methods in "Self-leveling Mortar" (JC / T 985-2017), and the main tests were fluidity, tensile bond strength, compressive strength, flexural strength, dimensional change rate, wear resistance and other properties. The results are shown in Table 1.
[0037] Table 1 Test results of relevant properties of the self-leveling mortar obtained in Example 1-Example 5
[0038]
[0039]
[0040] It can be seen from Table 1 that the self-leveling mortar based on copper tailings waste provided by the present invention has excellent indicators and can meet the relevant indicator requirements for the surface layer and the cushion layer in "Self-leveling Mortar for Floor" (JC / T 985-2017).
Claims
1. A self-leveling mortar based on copper tailings waste, characterized in that: Calculated by weight: 50-150 parts of 0-0.045mm quartz powder, 50-150 parts of 0-0.075mm copper tailings powder, 40-60 parts of 0.075-0.15mm copper tailings, 150-200 parts of 0.15-0.3mm copper tailings, 30-60 parts of 0.3-0.6mm copper tailings, 180 parts of 0.3-0.6mm quartz sand -220 parts, P·O42.5 cement 230-270 parts, sulphoaluminate cement 80-120 parts, anhydrite 20-40 parts, tartaric acid 0.8-0.9 parts, redispersible latex powder 6-8 parts, cellulose ether 0.6-0.8 parts, water reducer 0.8-1.0 parts, water 200-240 parts; the copper tailings waste residues of different particle sizes are all waste residues after the valuable components of the copper tailings are recovered.
2. The self-leveling mortar based on copper tailings waste according to claim 1 is characterized in that: The main component of the redispersible latex powder is ethylene-vinyl acetate copolymer.
3. The self-leveling mortar based on copper tailings waste according to claim 1 is characterized in that: The cellulose ether is hydroxypropyl methylcellulose with a viscosity of 400 mPa·s.
4. The self-leveling mortar based on copper tailings waste according to claim 1 is characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent with a water reducing rate of 25-30%.
5. The self-leveling mortar based on copper tailings waste according to claim 1 is characterized in that: The copper tailings waste slag has a moisture content of less than 0.5%.
6. A method for preparing a ground self-leveling mortar based on copper tailings waste according to any one of claims 1 to 5, characterized in that: The method comprises the following steps: step 1, drying: drying the copper tailings waste slag after valuable components are recovered by using drying equipment, and the moisture content of the copper tailings waste slag after drying is less than 0.5%; step 2, sorting and adjusting the particle gradation of the copper tailings waste slag: screening the copper tailings waste slag with a size of 0.075-0.6 mm by using a vibration screening process, so as to ensure that the copper tailings waste slag with suitable gradation components is obtained after screening and adjustment; step 3, mixing and stirring: firstly, quartz powder, copper tailings waste slag powder, copper tailings waste slag with different gradations, quartz sand, silicate cement, sulphoaluminate cement, anhydrite, tartaric acid, redispersible latex powder, cellulose ether and water reducing agent are added into a mixer after being measured, mixed and stirred for 2-5 minutes, and then water is added and stirred for 4-8 minutes to obtain a ground self-leveling mortar based on the copper tailings waste slag.
Citation Information
Patent Citations
Method for preparing wall and floor tile adhesive mortar by using mill tailings
CN101880142B
External wall insulation plastering mortar prepared using fine sand from mine tailings and its preparation method
CN106892581B
Cited By
Mine tailing self-leveling mortar and preparation method thereof
CN120682001A
Mine tailings self-leveling mortar and preparation method thereof
CN120682001B